Al-Maqrīzī's al-Ḫabar ʿan al-bašar, Vol. V, Section 4: Persia and Its Kings, Part I - Hämeen-Anttila, Jaakko (Bibliotheca Maqriziana, 2017)
Al-Maqrīzī's (d. 845/1442) last work, al-Ḫabar ʿan al-bašar, was completed a year before his death. This volume, edited by Jaakko Hämeen-Anttila, covers the history of pre-Islamic Iran from the Creation to the Parthians. Readership: All interested in Mamluk historiography or pre-Islamic history of Iran.